Information Technology Governance and Performance of Local Government Organizations: Testing Mediation Role of Accounting Information System Quality - Sofyani, Hafiez; Sani, Maratussholichah Kurnia; Putra, Adli Zuliansyah; Septiari, Dovi (Jurnal Dinamika Akuntansi dan Bisnis, 2024)
This study aims to empirically test the role of effective information technology (IT) governance on local government organizations' (LGOs) performance with the quality of Accounting Information System (AIS) as a mediating variable. The samples of this study are LGOs in Yogyakarta, Indonesia. A total of 140 LGO officials, users of AIS software, are selected as the respondents. Data was collected through questionnaires. The minimum number of sample size is determined using the PLS-based 10 times rule of thumbs approach. This study uses Partial Least Square (PLS) to examine the relationship among variables. The results revealed that effective IT Governance did not increase LGOs' performance directly, but it should be through AIS quality as a mediator. This research results provide valuable input for LGOs particularly in emerging economies to enhance their performance by paying attention to the correlation between effective IT governance and AIS quality.